Cerebral Malaria - Dinda Salsabila; Alifia Mawadddah; Athalitha Andhera Nabil; Baiq Ramdhani Amelia Negara; Herdiana Nurul Utami; Indri Setiawati; Ni Nyoman Geriputri (Jurnal Biologi Tropis, 2023)
Cerebral malaria is the worst complication of malaria caused by Plasmodium spp. This disease is spread in tropical and subtropical countries and can attack all age groups and genders. The peak incidence occurs in preschool children and very often causes death in children. The endemic areas of malaria in Indonesia include NTT, Maluku, West Papua and Papua. Every year, as much as 40% of the total global population lives in or visits endemic areas every year. Cerebral malaria can cause long-term neurocognitive complications that can reduce quality of life. The speed of treatment determines the patient's prognosis. Therefore, it is necessary to understand the signs of malaria and the complications that can arise. This article was written to discuss cerebral malaria as a whole based on existing literature.